2007
DOI: 10.1371/journal.ppat.0030058
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a CCR5-Expressing T Cell Subset That Is Resistant to R5-Tropic HIV Infection

Abstract: Infection with HIV-1 perturbs homeostasis of human T cell subsets, leading to accelerated immunologic deterioration. While studying changes in CD4+ memory and naïve T cells during HIV-1 infection, we found that a subset of CD4+ effector memory T cells that are CCR7−CD45RO−CD45RA+ (referred to as TEMRA cells), was significantly increased in some HIV-infected individuals. This T cell subset displayed a differentiated phenotype and skewed Th1-type cytokine production. Despite expressing high levels of CCR5, TEMRA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 40 publications
3
65
0
Order By: Relevance
“…Additional work will be necessary to fully examine the function and homing properties of these cells and to see how they may differ from Tregs present in healthy controls and HIV-infected patients with chronic progressive disease. It is intriguing to hypothesize that this phenotype contributes to the control of viral replication and whether Tregs are more (or less) susceptible to HIV infection than conventional CD4 ϩ T cells (42,44,45,47,56,60). It has been reported that HIV replication is slower in Tregs than in conventional CD4…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional work will be necessary to fully examine the function and homing properties of these cells and to see how they may differ from Tregs present in healthy controls and HIV-infected patients with chronic progressive disease. It is intriguing to hypothesize that this phenotype contributes to the control of viral replication and whether Tregs are more (or less) susceptible to HIV infection than conventional CD4 ϩ T cells (42,44,45,47,56,60). It has been reported that HIV replication is slower in Tregs than in conventional CD4…”
Section: Discussionmentioning
confidence: 99%
“…ϩ effector memory CD4 ϩ subpopulations that are resistant to R5-tropic virus recently have been described (44). The low rate of viral replication seen in Tregs may be explained by the potential interaction of FoxP3, NF-B, and the HIV-1 long terminal repeat (LTR) (56).…”
Section: Discussionmentioning
confidence: 99%
“…Because of polymorphisms, some CCR5 haplotypes have additional CpGs (SI Appendix, Table S1). We compared the methylation content of CD45RO− vs. CD45RO+, or CD45RA+ vs. CD45RA− T cells derived from HIV-negative donors before and after accounting for whether the sorted T-cell subsets did vs. did not express CCR5 (CCR5+ vs. CCR5−), CD45RO−, or CD45RA+, and CD45RO+ and CD45RA− are surface markers representative of naïve and memory T cells, respectively; CCR5+ CD45RO− and CCR5+ CD45RA+ T cells are markers representative of terminally differentiated effector memory T cells (TEMRA) (24).…”
Section: Ccr5 Cis-regionsmentioning
confidence: 99%
“…While it is assumed that CCR5 and CXCR4 mediated HIV-1 infection differ only in terms of cell tropism, the limited data available concerning events that immediately follow HIV-1 entry mean that it is currently unknown if post-entry events also differ between R5 and X4 viruses. Recently a CD4+ T cell subset known as T EMRA (Effector Memory RA positive T cells) has been described, which is susceptible to X4 HIV-1 infection but displays a specific post-entry block to R5 HIV-1 strains despite expressing high levels of CCR5 (Oswald-Richter et al 2007). This observation implies that the mechanisms controlling CCR5 and CXCR4 mediated HIV-1 infection may differ even within the same cell type.…”
Section: General Introductionmentioning
confidence: 99%